The PISA View of Mathematical Literacy in Indonesia - Stacey, Kaye (Journal on Mathematics Education, 2011)
PISA, the OECD’s international program of assessment of reading,scientific and mathematical literacy (www.oecd.org/pisa), aims to assess the ability of 15 year olds to use the knowledge and skills that have acquired at school in real world tasks and challenges. It also uses questionnaires to gather data on students’ attitudes to learning and the conditions of schooling. Since 2000, PISA has tested the mathematical literacy of 15 year old students from many countries around the world. This paper describes the design of the PISA assessments, discusses mathematical literacy and reports on a selection of results from the PISA assessments, associated surveys and related analyses to give a flavour of the information that has resulted from this major international initiative. Results for Indonesia are compared with the OECD average and with a selection of countries, addressing issues of overall achievement, equity, and classroom environment.Keyword: PISA View, Mathematical Literacy, Indonesia DOI: http://dx.doi.org/10.22342/jme.2.2.746.95-126